TELAAH ULANG MANHAJ TAHLILI (TAFSIR ANALISIS) - Muhammad Anieg (Wahana Akademika: Jurnal Studi Islam dan Sosial, 2014)
Tafsir is the main instrument in an attempt to answer the problems of the people, who must soon discovered the concept or theory. This departs from the question that is often uttered by Hassan Hanafi: " hal ladainā naẓariyah fi ’lTafsīr?" This is an Islamic thinker anxiety on the theory and methodology of interpretation that is less classical touches many social problems. From here arises the methods, including taḥlīlī (analysis). Taḥlīlī method (analysis) is to interpret the verses of the Qur'an to describe all aspects contained in the versesthat are interpreted and explained the meanings contained therein in accordance with the expertise and inclination commentators interpret these verses. The main purpose taḥlīlī method is to lay the foundations for a rational understanding of the miracle of the Qur'an, something which is not considered an urgent need for Muslims today. Because it is necessary to develop a method of interpretation because this method produces the idea that diverse and fragmented.Keywoard: al-Qur’an, manhaj, taḥlīlī, tafsir, analisis=1*18('18*$'(888('?8821B(*8(?*27('12=8(?(2?7(B2'$18122192k(*(8(929(?82*8(2*E1(?*81=*2'8(c$(1828812=8($88(*(11=6}77oN*=07.=1r*†}1117'98%(*•(828(8(2*'(82272)2=8(*?*(88288 17(11 97119782$9(1'1297 ?*27('1E*2'(*(*1(18('(82197$)8Z7r7r711EZ7r7r'(827111828(*?*(88(k(*1(12=8(/$*•82(19*(771?(981928(8(k(*1(188*(8(*?*(8((•?7(8('()1928(8(*(992*9(B8 8( (•?(*81( 9782 92''(882*1 8(*?*(8 8(1( k(*1(1E ('?$*?21(8Z7r7r'(8218278(=2$821=2**827$(*18.)2=8('*97(2=8(/$*•12'(8)B9128921(*($*)(8((=2* $17'182E(9$1(81(9(11*82(k(72?'(822=8(*.?*(882(9$1(81'(82?*2$9(18((88k(*1(=*)'(8(E8$968$96 7./$*0'@8Z7r7r8=1*711